2016
DOI: 10.1186/s12913-016-1355-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing health care and service providers’ and their respective “at risk” populations’ adoption of the Air Quality Health Index (AQHI): a qualitative study

Abstract: BackgroundThe Air Quality Health Index (AQHI) provides air quality and health information such that the public can implement health protective behaviours (reducing and/or rescheduling outdoor activity) and decrease exposure to outdoor air pollution. The AQHI’s health messages account for increased risk associated with “at risk” populations (i.e. young children, elderly and those with pre-existing respiratory and/or cardiovascular conditions) who rely on health care and service providers for guidance. Using Rog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Similar to other cities in the world (UK, Canada, U.S.A); Hong Kong’s AQHI policy alerts the public to risk and thereby promotes behavioral changes for “at risk populations” (Radisic and Newbold 2016). As such, health effects of the policy only occur if the population at risk changes its behavior in response to the information as well as the associated lower exposure reducing disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other cities in the world (UK, Canada, U.S.A); Hong Kong’s AQHI policy alerts the public to risk and thereby promotes behavioral changes for “at risk populations” (Radisic and Newbold 2016). As such, health effects of the policy only occur if the population at risk changes its behavior in response to the information as well as the associated lower exposure reducing disease.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study done by Radisic and Newbold in 2016 concluded that proper adaption to the AQHI depended on knowledge about the AQHI and characteristics of the policy; and perception about air quality and health. People less educated about the AQHI were less likely to adopt the behavioral changes suggested by the policy, which may include the elderly (Radisic and Newbold 2016). Older people are most vulnerable to COPD and pneumonia but they may not respond immediately to new information (Radisic and Newbold 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication tools such as various air quality indices focused on short-term variation in air quality can help patients adjust activities when air quality is poor ( 19 ). Detailed air pollution maps that provide information on long-term exposures and their impacts at neighborhood scales can also be used to target CVD treatment ( 20 ), exposure reduction, and efforts to address other behavioral risks contributing to CVD in those living in locations with highest exposures ( 21 ). Finally, the health sector as a whole, which bears the impact of air pollution, can provide much-needed support for ministries of environment, energy, and transportation, which are traditionally responsible for mitigation efforts.…”
Section: Addressing the Challenge: The Role Of Cardiac Organizationsmentioning
confidence: 99%
“…Communication tools such as various air quality indices focused on short-term variation in air quality can help patients adjust activities when air quality is poor [ 19 ]. Detailed air pollution maps that provide information on long-term exposures and their impacts at neighborhood scales can also be used to target CVD treatment [ 20 ], exposure reduction, and efforts to address other behavioural risks contributing to CVD in those living in locations with highest exposures [ 21 ]. Finally, the health sector as a whole, which bears the impact of air pollution, can provide much-needed support for ministries of environment, energy, and transportation, which are traditionally responsible for mitigation efforts.…”
Section: Addressing the Challenge: The Role Of Cardiac Organizationsmentioning
confidence: 99%